Generating intangible resource and international performance: insights into enterprises organizational behavior and capability at trade shows - Shih, Tsui-Yii; Yang, Chien-Ching (Journal of Business Economics and Management, 2019)
This paper helps to achieve a better understanding of the relationships among organizational behaviors, capabilities and the intangible resources of firms as a micro-level origin of the internationalization of enterprises. The resource-based view, strategic management theory, knowledge absorption and establishment practice, trade show issues and model theory development are integrated and implications offered for both scholars and practitioners. It integrates a research model based on trade show practices, and concentrates on the experimental conditions targeted by the respondents. The mediating roles of enterprises’ intangible resources are also discussed. Based on a sample of trade development groups, 256 completed questionnaires were used to examine the hypotheses. The hypotheses were tested using structural equation models. The findings show that relationship building positively influences relationship performance. The relationship performance has a significant mediating role on the effects of information sharing on international performance. Moreover, commitment to learning and high absorptive capacity of a firm determines the innovation performance of firms and contributes to their international performance.